The Challenges and Prospects of Women Fisherfolk in Makoko, Lagos State, Nigeria. Issue 2 (14th March 2022) - Oloko, Ayodele; Fakoya, Kafayat; Ferse, Sebastian; Breckwoldt, Annette; Harper, Sarah
Abstract: Makoko, a coastal fishing community in Lagos, Nigeria, aptly described as the "Venice of Africa", is also known as the world's largest floating slum. Contributions of women fisherfolk in artisanal fisheries are seldom appreciated despite the fact that in most coastal communities, women are the pillars and de facto household- heads, having to provide and sustain their households with little or no institutional or cultural support. This paper describes how women with different sizes of businesses (small, medium and large) conducted their fish trade in conjunction with their reproductive roles. Key findings suggest that sustainability of fisheries-based livelihoods for women fisherfolk is determined by working capital and access to credit facilities. Social networks and informal credit institutions were important factors to obtain capital by which the women were able to sustain and expand their businesses. Lack of formal education, poor access to information, discriminatory gender–based norms and cultural practices challenged sustainability of the women's livelihoods. This paper suggests approaches and interventions built on existing social networks and informal credit institutions to enhance women's economic contributions and mitigate constraints in their fisheries businesses.